The Effect of Trust in Government on Social Media X on the Online Participation of First-Time Voters - Alkadrie, Muhammad Zaheer; Bakry, Gema Nusantara (Persepsi: Communication Journal, 2024)
Political participation is important as a good citizen. Moreover, 2024 is a political year because in 2024 elections will be held to determine who will become president and leader of this country. In this election, for the first time Gen-Z participated in this election as a novice voter. This research departs from the researcher's curiosity about how social media influences their political participation in 2024, especially their political participation online on social media X. From there, the researcher formulated a new research. From there, the researcher formulated Research Objectives, namely this research focuses on factors such as political participation intentions, especially the political participation of novice voters who use social media X using quantitative research methods with a Likert scale as a benchmark. In addition, in its implementation, researchers used non-probability sampling techniques with convenience sampling. To calculate the sample, the sample was calculated with G-Power. Then the sample is calculated using SPSS. Because with this application we can test the validity of the data in terms of reliability, validity and internal consistency as measured by confirmatory factor analysis. We can determine the results we test using this Application to determine whether the information we provide is accurate.